Dominate or serve? Milestones of a long ecclesiastical search in the Quechua and Andean world - Albó, Xavier (1984)
When 500 years ago the Catholic Church and much more recently other Christian denominations came into contact with the Andean populations that today make up the states of Ecuador, Peru and Bolivia, they did not arrive at an empty world on which they could establish their own utopia at will. Christian. A solidly established society already existed for a long time, with its own social, economic and political institutions; with its own cultural synthesis, its value system, its ethics and its religion. All this formed a set with its own lights and shadows, systematized, coherent and ancestrally established in the region. Moreover, the same Christian message did not come in a very different and distant way from the one with which 16 centuries before Christ had announced the Good News. A set of so-called Christian ideas and practices now arrived riding on the back of a foreign power and society - also with its lights and shadows - that entered the foreign house like an invader.